INTEGRASI KURIKULUM MERDEKA PADA PEMBELAJARAN PAI DENGAN PENDEKATAN KONTEKSTUAL - Journal, Berajah; Rohbiah, Rohbiah; Cahyadi, Ani (CV. Lafadz Jaya, 2024)
Education in Indonesia continues to undergo evolution to meet the demands of the times and the needs of society. One of the major efforts in education reform is the development of the Merdeka Curriculum, an educational innovation aimed at increasing the relevance and quality of learning at the elementary school level. The Merdeka Curriculum emphasizes the development of students' character, creativity and skills to be able to compete globally. The method used in this research uses data collection analysis (literature review) from journals, internet media and online news media. The results in this research, namely the Merdeka Curriculum, emerged as a response to PISA findings which showed that the majority of Indonesian students were below minimum competency in reading comprehension and basic mathematical concepts. In an effort to overcome lagging behind in learning, the Ministry of Education and Culture, Research and Technology implemented an emergency curriculum during the COVID-19 pandemic, which succeeded in reducing the impact on literacy and numeracy.